Studi Deskriptif Strategi Komunikasi Pemasaran Pada Toko Komputer Karawang Dalam Meningkatkan Pelanggan - Ferniko Fernandes; Luluatu Nayiroh; Nur Kinan (Peneliti.net, 2023)
The marketing communication strategy is one of the important things inrunning a business, because the success of a business can be plannedfromthe marketing communication strategy. Researchers are interestedin conducting this research with the aim of knowing the marketingcommunication strategy carried out by Store Mark Computer Karawangin increasing customers. By using qualitative research with adescriptive study approach, it is expected to be able to answer theformulation of theresearch problem. With in-depth interview techniques,observation and literature studies and documentation studies, thisresearch is expected to be able to answer questions regarding themarketing communication strategy of the Mark Computer StoreKarawang. The determination of informants was carried out using anurgent sampling technique.The results of this study indicate that the Mark Computer KarawangStore applies four of the six all elements contained in the IntegratedMarketingCommunication (IMC), including advertising using an offlineadvertising system such as making billboards, brochures and banners,Sales Promotion Promotion) is carried out by meeting face to face, sothat the staff can easily explain in detail about the product and thenfollow up again via telephone or via WhatsApp social media so that it isexpected that all customers can understand the product well, internetmarketing (personal selling). ) Offers made with precise and clearbuyers, how to market them in a language that is easily understood bycustomer